2014
DOI: 10.1016/j.healthplace.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Place-based stressors associated with industry and air pollution

Abstract: Exposure to air pollution and its sources is increasingly viewed as a psychosocial stress, however its nature is not understood. This article explores the role of the concept of place on risk perception and community stress within data collected from eight focus groups in Philadelphia, USA. Discussions focused on air pollution, a nearby oil refinery, health, and a proposal for air monitoring. We present a framework of place-based elements of risk perception that includes place identity, stigma and social contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 50 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…Though several scholars have found the PHMC surveys reliable and valid (Kondo, et al, 2014, Yang, et al, 2011), due to the fact that we pooled two waves of data together, we compared some key measures drawn from our data with those reported by the 2010 Behavioral Risk Factor Surveillance System (BRFSS) in the Philadelphia metropolitan area (CDC, 2010) to address the concern about data quality. We found that the pooled data retain high reliability and validity.…”
Section: Methodsmentioning
confidence: 99%
“…Though several scholars have found the PHMC surveys reliable and valid (Kondo, et al, 2014, Yang, et al, 2011), due to the fact that we pooled two waves of data together, we compared some key measures drawn from our data with those reported by the 2010 Behavioral Risk Factor Surveillance System (BRFSS) in the Philadelphia metropolitan area (CDC, 2010) to address the concern about data quality. We found that the pooled data retain high reliability and validity.…”
Section: Methodsmentioning
confidence: 99%
“…Other facilities, traffic, and other urban sources of VOCs also impacted the area. Further description of this refinery and its location are provided elsewhere (Kondo et al, 2014). Five sites were designated as "near fenceline," since they were 30-40 m from the refinery's boundary and near its central section where distillation units and an associated tank farm were located.…”
Section: Methodsmentioning
confidence: 99%
“…Fixed-point hazards such as pipeline oil spills are of great significance to nearby communities, constituting more problems where poverty already affects the population [15] [16]. The frequency and risk of these terrestrial oil spills [17] [18] have great impact on the physical and human environment [19] [20].…”
Section: Introductionmentioning
confidence: 99%